Study of socio-demographic factors causing interruption of anti-tuberculosis treatment in DOTS centre in Warangal district of Telangana State - Ramchandra, Tagaram; Kumar, N. Pragathi; Lakkoju, Niharika (International Journal Of Community Medicine And Public Health, 2017)
Background: Tuberculosis has existed for millennia and remains a major global health problem. It causes ill-health in millions of people each year and in 2015 it was one of the top 10 causes of death worldwide. Understanding the specific reasons for unsuccessful outcomes is important to improve the treatment system. This present study was carried out to find out the effects of socio-demographic factors on TB defaulters under DOTS centre in Warangal District, Telangana state. Methods: A cross sectional study was carried among 103 defaulters of TB patients in 3 TB units (TU) Warangal (urban), Ragunathapally (rural) and Eturunagaram (tribal) out of 7 TB units in Warangal district, attached to District Tuberculosis Centre (DTC) from January 2016 to June 2016 by interview technique utilising a pretested and structured questionnaire to collect the data. Statistical analysis: Percentages, proportions and chi-square test were applied whenever necessary. Results: In present study, males (35%) were more than females (7.8%) and 42.8% were in the age group of 40-55 years, followed by 28.1% were 26-39 years age group. Majority of defaulters were in nuclear family (77.7%) followed by joint family (21.3%). Cost of travel as a reason for default of treatment was seen more in tribal area (16.5%) than rural (12.6%) and urban (4.8%) TUs. The TB patients residing in tribal areas are more prone to default, an important reason being the distance needed to travel to the closest health facility, availability and the need to travel by public transport. Conclusions: Tuberculosis is an infectious disease which has a devastating impact on the economic wellbeing of individual and their families. Most of the defaulters were illiterates residing in tribal area. Cost of travel as a reason for default of treatment was seen more in tribal TU 17(16.5%) than urban and rural TUs.